Primary prevention of latex related sensitisation and occupational asthma: a systematic review. Issue 5 (9th February 2006) - LaMontagne, A D; Radi, S; Elder, D S; Abramson, M J; Sim, M
Abstract : Methods: Eight primary prevention intervention studies on natural rubber latex (NRL) published since 1990 were identified and reviewed. This is the largest evidence base of primary prevention studies for any occupational asthmagen. Results: Review of this small and largely observational evidence base supports the following evidence statement: Substitution of powdered latex gloves with low protein powder-free NRL gloves or latex-free gloves greatly reduces NRL aeroallergens, NRL sensitisation, and NRL-asthma in healthcare workers. Evidence in support of this statement is ranked SIGN level 2+, referring to well conducted case-control or cohort studies with a low risk of confounding, bias, or chance and a moderate probability that the relationship is causal. Conclusion: Substitution of powdered latex gloves with low protein powder-free NRL gloves or latex-free gloves promises benefits to both workers' health and cost and human resource savings for employers. This message should be broadly disseminated beyond the hospital sector to include other healthcare settings (such as aged care facilities) as well as food service and other industries where latex gloves might be used.